(untitled) (Eurasian Journal of Ecology, 2023)
The effects of medium aerosol areas on the hydrological system in the forest cover of Eastern Zangezur were investigated using modern methods. The hydrological network schemes of the research area in 2000 and 2020 were drawn up, and the lengths of the river network were determined according to the grid code (degrees). The graph of the river network length change (in km) by classes (grid code) in the study area in 2000 and 2020, and the length of the river network by classes (grid code) in the growth of average aerosol areas is reflected. According to the compiled histogram, when comparing the years 2000 and 2020, the growth of the 1st, 6th, 8th, and 9th grade river networks decreased, but the total length increased by 213.18 km. The average aerosol total length increases when the area increases and decreases when it decreases, indicating that an increase in aerosol area is required for an increase in the river network. Key words: ArcGIS, aerosol, landsat, hydrological network, Hakari river.